Inadvertent Harm: An Institutional Analysis of Iatrogenic Vascular Injuries and Management - Vemuri Nandan; Suhas S Gowda; Sanjay C Desai; Chandrashekar Anagavalli Ramswamy; Tadasina Sajay Reddy; Parth Joshi (Indian Journal of Vascular and Endovascular Surgery)
Iatrogenic vascular injuries are unintended complications arising from medical or surgical procedures, posing significant risks to patient outcomes. These injuries can result from various interventions, such as catheter placements and stent insertions, and may lead to serious complications. This study analyzes a series of iatrogenic vascular injuries encountered at our institution, focusing on their management and outcomes to enhance patient safety and procedural techniques. From September 1, 2022, to May 31, 2024, a total of nine patients (six males and three females) were treated for iatrogenic vascular injuries at our institution. The injuries resulted from various procedures, including catheter placements, endovascular interventions, and chemo port insertions. Management strategies included both endovascular and open-surgical approaches, with outcomes measured based on postoperative recovery, complications, and overall patient prognosis. The injuries involved a range of complications, including pseudoaneurysms, misplaced guidewires, and arterial damage. Endovascular techniques, such as stent placement and guidewire retrieval, were successfully utilized in four cases, while open surgical interventions were necessary in the remaining four cases to control severe bleeding and repair complex arterial defects. Postoperative complications were minimal, and all patients recovered well, with no mortality reported. Iatrogenic vascular injuries, though challenging, can be effectively managed with a combination of endovascular and open surgical techniques. The choice of approach should be dictated by the specific nature of the injury, aiming to minimize complications and ensure optimal patient outcomes. The findings from this case series underscore the importance of tailored management strategies in improving patient safety in vascular interventions.